2020
DOI: 10.5296/jas.v8i3.15886
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spray Drying Parameters on Lactose-Free Milk Powder Properties and Composition

Abstract: Lactose-free milk powders are an interesting topic, as the industry still struggles with the enhanced stickiness of the material. To better understand this topic, an industrial scale spray-dryer was used to assess the influence of process parameters on the powder properties of lactose-free milk. A simple design of experiments was conducted varying the inlet temperature in combination with the atomization flow rate. The intention was to set different driving forces for drying in combination with the different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…The amounts of moisture, fat, ash, protein, fibre, and carbohydrates in the lactose-free milk powder, oats, mushrooms, and jaggery are shown in Table 2. The amount of nutrient constituents that exist in the lactose-free milk powder falls within the range mentioned in earlier studies [24,25]. The percentage range of each constituent present in the oat powder was also reported in previous studies [26][27][28], and our results are concordant with their results.…”
Section: Proximate Analysis Of Lactose-free Milk Powder Oat Powder An...supporting
confidence: 93%
“…The amounts of moisture, fat, ash, protein, fibre, and carbohydrates in the lactose-free milk powder, oats, mushrooms, and jaggery are shown in Table 2. The amount of nutrient constituents that exist in the lactose-free milk powder falls within the range mentioned in earlier studies [24,25]. The percentage range of each constituent present in the oat powder was also reported in previous studies [26][27][28], and our results are concordant with their results.…”
Section: Proximate Analysis Of Lactose-free Milk Powder Oat Powder An...supporting
confidence: 93%
“…Sant'Anna et al [56] found Brazilian WP powder of the variety Labrusca with a maximum moisture content of 9.7% to be microbiologically stable for storage at ambient conditions. Nevertheless, the RMs of both micronized fillers in this study were below 5%, which is considered the limit for safe storage of dairy ingredients [57,58]. These results confirm mill-drying with a TurboRotor as a viable preparation method to obtain fine biogenic powders with suitable moisture contents in addition to economic benefits.…”
Section: Physical Properties Of Prepared Wp Fillerssupporting
confidence: 63%
“…Over the years, the drying of crops has been advancing using continuously improved techniques to attain the goal of safely removing desired moisture content from crops without compromising their nutritional qualities. 7,10 Drying methods can be broadly categorised as natural drying and artificial drying. 4 Natural drying makes use of direct heat from the sun for drying; the sample is spread on the horizontal plane that is opened to direct sunshine without any shade and heat energy from the sun is used in the drying process.…”
Section: Literature Reviewmentioning
confidence: 99%